The Holy Gospels in Anglo-Saxon, Northumbrian, and Old Mercian Versions: Synoptically Arranged ... - Walter William Skeat (The University Press, 1871)
Book digitized by Google and uploaded to the Internet Archive by user tpb.
Keywords: MARK